2018
DOI: 10.3928/01484834-20180420-08
|View full text |Cite
|
Sign up to set email alerts
|

Type D Personality as a Predictor of Resilience Among Nursing Students

Abstract: It would be beneficial to include specific interventions for decreasing negative affectivity and promoting stress coping skills training in the training programs in nursing school curricula. [J Nurs Educ. 2018;57(5):296-299.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…Type D personality was found in 30.8% of this study's sample, similar to previous findings (Mols & Denollet, 2010; Škodová & Bánovčinová, 2018). The mean HPB score (2.48 ± 0.48) was somewhat lower than that found in Malaysian college students (Kuan, Kueh, Abdullah, & Tai, 2019), and the QoL subscale scores were lower than those found in Chinese college students (Choi, Wong, & Fong, 2017).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Type D personality was found in 30.8% of this study's sample, similar to previous findings (Mols & Denollet, 2010; Škodová & Bánovčinová, 2018). The mean HPB score (2.48 ± 0.48) was somewhat lower than that found in Malaysian college students (Kuan, Kueh, Abdullah, & Tai, 2019), and the QoL subscale scores were lower than those found in Chinese college students (Choi, Wong, & Fong, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…Studies of the relationships between Type D personality, HPB, health status, and QoL among university students are scarce, despite the fact that between 22.4% and 36.2% of university students have a Type D personality (Mols & Denollet, 2010; Škodová & Bánovčinová, 2018), they are frequently exposed to unhealthy behaviors, and their HPB are low. Additionally, Type D personality is an important factor influencing HPB, health status, and QoL in general populations; it should thus be considered for university students as well.…”
Section: Introductionmentioning
confidence: 99%
“…Significant positive correlations were found for emotional exhaustion and depersonalization with SOC as well as with all work environment factors; however, personal accomplishment showed very low scores and did not correlate with SOC. In the same vein, Galletta et al [ 46 ] investigated the relationship between SOC and burnout in Italian speech-language pathologists, finding that speech-language pathologists with low SOC showed significantly higher burnout scores. Kawamura [ 44 ] found similar results with respect to a sample of attending physicians in Japan, such that lower scores on the SOC, being female, working more hours, and having fewer years of experience are related to greater burnout.…”
Section: Resultsmentioning
confidence: 99%
“…Another study revealed that the presence of Type D characteristics, particularly negative affectivity, was a significant predictor of resilience among nursing students (Skodova & Banovcinova, 2018).…”
Section: Backg Rou N Dmentioning
confidence: 98%
“…Similarly, a study of 97 nursing, midwifery and psychology students showed that those with Type D personality characteristics scored significantly higher on the burnout syndrome questionnaire than those with non‐Type D personality characteristics (Skodova, Lajciakova, & Banovcinova, 2016). Another study revealed that the presence of Type D characteristics, particularly negative affectivity, was a significant predictor of resilience among nursing students (Skodova & Banovcinova, 2018). However, whether those with Type D characteristics have a poorer ability to cope with the emotional demands faced by the nursing profession, which in turn may impact on their health‐related behaviour, remains unclear.…”
Section: Introductionmentioning
confidence: 99%